JENIS-JENIS BAMBU DI HUTAN ADAT PENYANGGAR KABUPATEN BENGKAYANG PTOVINSI KALIMANTAN BARAT - Lolyta Sisillia; Junisa Junisa (Universitas Tanjungpura, 2022)
Many species of bamboo grow in the Penyanggar customary forest area. Identification of bamboo is important to know the characteristics of bamboo that grows in the area. The purpose of this study was to found bamboo species based on their morphological characters at Penyanggar. Data from identification of bamboo is expected to be used as information in the course of collecting data on the potential of bamboo in the Penyanggar Customary Forest, Bengkayang Regency and information for the community as users, especially those around the Penyanggar Customary Forest so that it is used appropriately. The research was carried out from July to October 2020 in the Penyanggar customary forest. The research was done by using exploration survey and experimental methods by exploring every corner of the location that can represent the bamboo vegetation in the Penyanggar customary forest to collect all species of bamboo to be identified. This study found five genera are Bambusa, Gigantochloa, Dendrocalamus, Schizostachyum, and Thyrsostachys. The identified bamboo species are: B. multiplex, B. vulgaris., B. heterostachya, B. blumeana, G. balui, G. ater, G. hasskarliana, G. levis, G. luteostriata, D. asper, D. hirtellus, S. blumei, S. brachycladum, S. flexuosum, S. latifolium, and T. siamensis.Keywords: bamboo, customary forest, identificationAbstrakBermacam jenis bambu tumbuh di kawasan Hutan Adat Penyanggar. Identifikasi bambu penting untuk mengetahui karakteristik bambu yang tumbuh di kawasan tersebut. Tujuan penelitian untuk mengetahui jenis-jenis bambu di Hutan Adat Penyanggar Kabupaten Bengkayang. Data hasil identifikasi bambu diharapkan dapat sebagai informasi dalam rangka pendataan potensi bambu yang ada di Hutan Adat Penyanggar Kabupaten Bengkayang dan informasi bagi masyarakat sebagai pengguna khususnya yang berada di sekitar Hutan Adat Penyanggar agar tepat dalam pemanfaatannya. Penelitian dilaksanakan pada bulan Juli sampai dengan Oktober 2020 di Hutan Adat Penyanggar. Penelitian ini menggunakan metode survey dan eksperimen dengan teknik menjelajah setiap sudut lokasi yang dapat mewakili vegetasi bambu di hutan adat Penyanggar untuk mengoleksi semua jenis bambu yang akan diidentifikasi. Berdasarkan hasil penelitian jenis bambu yang ditemukan di Hutan Adat Penyanggar terdiri atas 5 genus yaitu Bambusa, Gigantochloa, Dendrocalamus, Schizostachyum, dan Thyrsostachys. Spesies bambu yang teridentifikasi, yaitu: B. multiplex, B. vulgaris., B. heterostachya, B. blumeana., G. balui, G. hasskarliana, G. levis, G. luteostriata, D. asper, D. hirtellus, S. blumei, S. brachycladum, S. flexuosum, S. latifolium, dan T. siamensis. Kata Kunci: bambu, hutan adat, identifikasi